Product Proposal For Restoring Residential Facades In Historical Sites Using A Lime-Based System - Alves Junior, José Genival; Moreira, André Pina; Lemoine, André Neves; Pereira Junior, Clodomir Barros (Seven Editora, 2023)
Historic Urban Centers are important in the new era of the globalized world and the economic development of sustainable tourism. These centers are laden with symbolism and cultural identity. Key elements in the landscape. In this way, to attract visitors, it is essential to preserve the architectural and urban complex. Facade coatings have as their main function the protection of masonry elements. In the context of historic buildings, in addition to protection, the external coating is an integral and inseparable element of the material authenticity of the monument. They are ancestral materials and techniques, in addition to chromatic concepts that, over the years, give it value and coherence within a whole. Based on the aspects described above, the research consists of presenting a lime-based coating system that responds positively to the physical and chemical requirements of old supports, ensuring satisfactory resistance in addition to aesthetic and historical coherence, guaranteeing greater authenticity. , preserving the historical and aesthetic reading of the monument. From the study of building typologies and ancestral construction techniques, combined with the study of mortars, their main characteristics, constituents, and pathologies, it was possible to adopt an experimental trait for the construction of a coating system inspired by ancient constructive practices for mortar coating on facades. Finally, this research describes guidelines for further studies considered necessary for the improvement of this intervention process, which aims to reduce the distortions verified in the current practice of restoring old residential facades located in the Historic Site of Olinda. DOI: https://doi.org/10.56238/methofocusinterv1-039